Relationship between Employee Quality Development and Work Productivity of the Forestry and Plantation Service Office of Purwakarta Regency - Budi Rismayadi (GoAcademica Research & Publishing, 2020)
The purpose of this research is to determine the relationship between employee quality development and work productivity of employees at the Forestry and Plantation Service of Purwakarta Regency. The research method used is a verification research method with multiple linear regression models, the data processing uses multiple correlation analysis and uses the F test and T test. The population is all employees of the Purwakarta district health and plantation office, with a sample of 50 people. The variable used is the Quality Development variable as the X variable, which consists of two variables, namely: the X1 training variable and the X2 course variable, while the work productivity is the Y variable. The results of the study show that training and courses on work productivity are obtained F count> F table namely 4,375> 3,767 indicates that there is a significant relationship between development variables on work productivity, development variables on work productivity. The results of correlation analysis between variables have a correlation coefficient between training and work productivity 0.491; between courses with work productivity 0.473. Of the two independent variables, the training variable has a correlation coefficient value greater than the course variable. The coefficient value of 0.491 indicates a moderate interpretation for the training and work productivity variables. The coefficient of determination (R2) between the training and course variables is 28%, the remaining 72% is influenced by other factors. In other words, the variable of employee quality development in the Forestry and Plantation Service of Purwakarta Regency is not the superior variable in increasing work productivity. From the results of the regression analysis, the percentage increase in variable X to Y is obtained as follows: to achieve maximum productivity, amounting to 27.129%; training 27.050%, and courses 27.061%. Of the existing variables, training only required an increase of 27.050%.